Management and outcome of pediatric inguinal hernias with emphasis on technique without opening the inguinal canal- a single center experience - Girdhar, Rajesh; Singh, Ikjot; Mallick, Achinta Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Herniotomy for congenital inguinal hernia in children is a fairly common surgical procedure. Inguinal hernias in infants can be repaired by conventional surgery as well as laparoscopic approach. Open repair of inguinal hernias in children without opening the inguinal canal, thereby maintaining the normal anatomy was done at our centre. Objective was to evaluate the course and outcome of paediatric congenital inguinal hernia cases operated at our centre. Methods: This study was conducted in a service hospital (Military Hospital Jammu), on 67 patients presenting with congenital inguinal hernia during October 2014 to June 2017. Results: Sixty-two children were male and five were female. 18 were less than one year, 38 between two to five year and 11 more than five years. All the patients were evaluated preoperatively and taken up for surgery under general anesthesia (n=18) spinal block (n=36) and caudal anesthesia (n=13). Approximate length of skin incision was 1.5 to 2.0 cm. External inguinal ring was opened in 3 cases only. Approximate postoperative stay in hospital was 1-2 days. Nine patients had reactive hydrocele and one patient developed surgical site infection (SSI). On 12 months post-operative follow up, none of the patients had any further complications. Conclusions: Inguinal hernias are common in children, with increased risk of incarceration if not repaired early. Open technique without altering the inguinal canal anatomy is also a suitable alternative to congenital inguinal hernia repair in children with favourable comparable outcome.